PENGARUH LATIHAN RESISTANCE BAND DAN SKIPING TERHADAP KEMAMPUAN SMASH BOLA VOLI TIM SMP NEGERI 6 KOTA PALOPO. - Oxadelva Nandia Djody; Irsan Kahar; Suaib Nur (Jurnal Porkes, 2025)
The low smash ability of junior high school volleyball players is often caused by a lack of training that integrates upper and lower body muscle strengthening simultaneously. This study aims to analyze the effect of a combination of resistance band and skipping exercises on improving volleyball smash ability in the team of SMP Negeri 6 Kota Palopo. The method used was a quasi-experiment with a one-group pretest-posttest design on 12 male players. The training intervention was conducted for 16 days with a frequency of six sessions per week, which included resistance band training to increase arm, shoulder, and core strength, as well as skipping training to develop explosive power and leg muscle coordination. Data were collected through smash tests before and after the treatment, then analyzed using a paired sample t-test. The results showed a significant improvement in smash ability, with the pretest average score of 14.58 increasing to 18.58 in the posttest (p = 0.000). It was concluded that the combination of resistance band and skipping exercises effectively improved smash ability by optimizing hitting power and jump quality. These findings provide a practical and affordable alternative training model for application in school-level volleyball training.